2015
DOI: 10.1103/physrevd.91.096001
|View full text |Cite
|
Sign up to set email alerts
|

NonthermalCPviolation in soft leptogenesis

Abstract: Soft leptogenesis is a mechanism which generates the matter-antimatter asymmetry of the Universe via the out-of-equilibrium decays of heavy sneutrinos in which soft supersymmetry breaking terms play two important roles: they provide the required CP violation and give rise to the mass splitting between otherwise degenerate sneutrino mass eigenstates within a single generation. This mechanism is interesting because it can be successful at the lower temperature regime T 10 9 GeV in which the conflict with the ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 84 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…In the following, however, we will focus on a generic trilinear soft A α term [343] in soft leptogenesis [344], which results in interesting consequences: In order to discuss the aforementioned consequences, we assume the temperature range T 10 8 GeV for m soft ∼ 1 TeV, where the effective global symmetries discussed in Ref. [333] are absent.…”
Section: Type I Soft Leptogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In the following, however, we will focus on a generic trilinear soft A α term [343] in soft leptogenesis [344], which results in interesting consequences: In order to discuss the aforementioned consequences, we assume the temperature range T 10 8 GeV for m soft ∼ 1 TeV, where the effective global symmetries discussed in Ref. [333] are absent.…”
Section: Type I Soft Leptogenesismentioning
confidence: 99%
“…[339,340], thermal effects are crucial to prevent the cancellation of leading CP asymmetries from the decays of N ± to leptons and sleptons. However, terms higher order in m soft /M N can dominate when considering generic A α [343].…”
Section: Type I Soft Leptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…One may get non-zero asymmetry from the interference of tree and higher order diagram without right of the 'cut' condition, but it would vanish if other diagrams with all possible intermediate and final states are considered. The cases where some authors have found vanishing of total asymmetry [9][10][11] are examples of this feature. In our case in leptogenesis, above-mentioned condition is satisfied in the higher order Feynman diagram for neutralino decay as shown in Fig.…”
Section: Introductionmentioning
confidence: 91%
“…In Ref. [28], it is shown that considering most generic soft trilinear couplings and one loop self energy contributions for sneutrino decay it is possible to generate CP violation even without finite temperature effects within the same setup.…”
Section: Introductionmentioning
confidence: 99%